2022
DOI: 10.3390/pharmaceutics14091889
|View full text |Cite
|
Sign up to set email alerts
|

Association between Genetic Polymorphisms and Bleeding in Patients on Direct Oral Anticoagulants

Abstract: Objectives: The purpose of our study is to investigate the effects of apolipoprotein B (APOB) and APOE gene polymorphisms on bleeding complications in patients receiving direct oral anticoagulants (DOACs). Methods: A total of 16 single nucleotide polymorphisms (SNPs) in 468 patients were genotyped. Six SNPs of ABCB1 (rs3842, rs1045642, rs2032582, rs1128503, rs3213619, and rs3747802), one SNP of CYP3A5 (rs776746), seven SNPs of APOB (rs1042034, rs2163204, rs693, rs679899, rs13306194, rs13306198, and rs1367117),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…As shown in Table 2 , all unadjusted included studies reported nonsignificant data regarding the association of odds of ADRs and genetic variants. On the contrary, Yoon et al's study, which was the only adjusted study (adjusted for sex, age, overdose, rivaroxaban, anemia, and other genetic variants), demonstrated that being a carrier of rs1045642 or rs13306198 almost triples the odds of bleeding (OR for rs1045642 = 2.44, 95% CI: 1.07 to 5.58; OR for rs13306198 = 3.00, 95% CI: 1.39 to 6.47) [ 28 ]. Similarly, an adjusted prospective cohort indicated that the presence of rs1045642 decreases the hazard of a thromboembolic event by 58 percent (adjusted HR = 0.42, 95% CI: 0.18 to 0.98), which is a consequence of reduced rivaroxaban exposure [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 2 , all unadjusted included studies reported nonsignificant data regarding the association of odds of ADRs and genetic variants. On the contrary, Yoon et al's study, which was the only adjusted study (adjusted for sex, age, overdose, rivaroxaban, anemia, and other genetic variants), demonstrated that being a carrier of rs1045642 or rs13306198 almost triples the odds of bleeding (OR for rs1045642 = 2.44, 95% CI: 1.07 to 5.58; OR for rs13306198 = 3.00, 95% CI: 1.39 to 6.47) [ 28 ]. Similarly, an adjusted prospective cohort indicated that the presence of rs1045642 decreases the hazard of a thromboembolic event by 58 percent (adjusted HR = 0.42, 95% CI: 0.18 to 0.98), which is a consequence of reduced rivaroxaban exposure [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…With a comprehensive confounding control, the risk of major/CRNM bleeding was closely similar in wild-type patients and variant carriers at rs1128503, rs2032582, and rs1045642 considered individually and as haplotypes, but patients treated with rivaroxaban (N = 802) and apixaban (N = 1324) were considered jointly ( 45 ). Similarly, a cross-sectional case-control study in Korean patients (50 with bleeding and 418 controls) jointly considered patients on apixaban, edoxaban, dabigatran and rivaroxaban (N = 74), and suggested no univariate association between the case status and ABCB1 polymorphisms rs1128503, rs2032582 or rs1045642 ( 46 ). In contrast, another cross-sectional study in Korean patients (64 cases and 229 controls) treated with either apixaban or rivaroxaban (numbers not reported) suggested higher risk in variant carriers at rs1045642 vs. wild-type subjects ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in pharmacogenetics have shed light on the intricate relationship between DOACs and genetic polymorphisms 13 . For example, specific genotypes of ABCB1 rs3842 and APOB rs13306198 variants have been linked to an increased risk of bleeding events in patients receiving DOACs 14 . In addition to ABCB1 , emerging risk factors such as AKR7A3 and ABCA6 were observed; however, the role of genetic variations in bleeding events by rivaroxaban treatment remains unclear and has drawn limited attention 15–18 ( Table 1 ).…”
Section: Gene Polymorphism Relevance Referencementioning
confidence: 99%
“…13 For example, specific genotypes of ABCB1 rs3842 and APOB rs13306198 variants have been linked to an increased risk of bleeding events in patients receiving DOACs. 14 In addition to ABCB1, emerging risk factors such as AKR7A3 and ABCA6 were observed; however, the role of genetic variations in bleeding events by rivaroxaban treatment remains unclear and has drawn limited attention [15][16][17][18] (Table 1). In this issue of Clinical and Translational Medicine, the multicenter prospective cohort study focused on genetic polymorphisms, researchers identified 18 SNPs from 14 genes (including COL6A3, NCAM2, MMP3, VCAN, JCAD) as promis-ing biomarkers for understanding the adverse effects of rivaroxaban.…”
mentioning
confidence: 99%